Non-destructive corrosion study on a magnesium alloy with mechanical properties tailored for biodegradable cardiovascular stent applications. (10th March 2021) - Cai, Changhong; Alves, Marta M.; Song, Renbo; Wang, Yongjin; Li, Jingyuan; Montemor, M. Fátima
Abstract: An Mg-2Zn-0.6Zr-0.6Nd alloy for biodegradable cardiovascular stent applications was prepared through indirect extrusion. The alloy exhibited a superior combination of tensile yield strength (TYS), ultimate tensile strength (UTS) and elongation (EL) of about 269 MPa, 298 MPa and 25.6 %, respectively. In addition, the non-destructive electrochemical frequency modulation (EFM) technique was used for the first time to investigate the corrosion behavior of Mg alloys combined with electrochemical impedance spectroscopy (EIS) in Dulbecco's Modified Eagle's Medium (DMEM) and in Hank's solution. Compared with the corrosion rate of 0.07 mm/year in Hank's solution, lower corrosion rate of 0.03 mm/year was achieved in DMEM. The significant differences between the corrosion rate trends were discussed and related with the composition of the corrosion layer formed. Depending on the biomimetic fluids tested, different corrosion products were precipitated on the alloy's surface: a compact and homogeneous layer of Mgx Cay (PO4 )z and Zn(OH)2 and organic compounds was formed in DMEM, whereas a partial coverage of Mgx Cay (PO4 )z and Mg(OH)2 was formed in Hank's solution.